The Migrant Crisis and Refugees – a Crisis of EU Solidarity - Mikołajczyk, Barbara (Polish Review of International and European Law, 2020)
The migration and refugee crisis in Europe 2015–2016 has posed a great challenge to the international and European community in terms of solidarity with refugees, forced migrants and countries most vulnerable to large waves of migration. It would seem that solidarity in the European Union is well established, but it turned out that the crisis situation triggered a different interpretation of solidarity within the EU and revealed the weaknesses of burden sharing mechanisms. The intra-EU solidarity proved to be the most difficult to achieve in practice. In this study considerable attention is paid to the principle of solidarity in the EU law and its interpretation by Member States as well as the Court of Justice. Moreover, the conducted analysis concerns three main EU solidarity and burden sharing measures – the Dublin mechanism, the applied in 2015 relocation schemes and ‘forgotten’ temporary protection measures. Their inadequacy in times of crisis became an important lesson both for the States as well as for the European Union itself and makes us rethink the concept of solidarity and its practical application.